THE IMPACT OF THE SUFI VIEWS ON THE WELTANSCHAUUNG OF THE WESTERN SCHOLARS - Raupova Ra’no Soyibovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the following article the recent analysis and the insights over the religious, scientific and literary views of the Hoja Ismat Bukhari is analysed based on his divans.